Study of Nightingale’s nursing professionalism: a survey of nurses and nursing students in China - Qian Wang; Chen Wang; Dan Luo; Jin Li; Zhiguang Duan (BMC Nursing, 2022)
Abstract Background Nursing professionalism is highly significant to the development of nursing. Florence Nightingale was the founder and leader of modern nursing, and Nightingale’s nursing professionalism has a significant impact on nursing in China and all over the world. In the new era, a new understanding of Nightingale’s nursing professionalism should be developed, and its positive role in nursing reshaped. Methods A total of 1,557 nurses and nursing students from 27 provincial administrative regions of China were surveyed using a customized questionnaire. Their recognitions of Nightingale’s nursing professionalism were evaluated based on scores, and statistical differences between and within the groups were analyzed using an Analysis of Variance (ANOVA). The elements of Nightingale’s nursing professionalism were extracted by the exploratory factor method and a principal component analysis. Results The Cronbach’s α of the questionnaire was 0.965, and the two groups did not differ significantly (p > 0.05). Based on the standard that the cumulative contribution rate of common factor should be > 85%, three common factors of Nightingale’s nursing professionalism, including professional emotion, professional ability and professional ethics, were extracted based on the Scree plot. Conclusions This study aimed to explore the connotation of Nightingale’s nursing professionalism. Our survey indicates that Nightingale’s nursing professionalism is highly recognized by nurses and nursing students in China. Its connotation includes professional emotion, ability and ethics. Nursing education and nursing management should fully utilize the leading role of Nightingale and guide the professional behaviors of nurses to be consistent with Nightingale’s nursing professionalism, thus, improving the degree of nurse professionalism.